Inclusive education in the Dominican Republic: teachers’ perceptions of and practices towards students with diverse learning needs - D’Angelo, Sophia; Singal, Nidhi (Frontiers in Education, 2024)
Students with diverse learning needs, particularly those with disabilities or identified as overaged, face significant challenges within the Dominican Republic’s education system, characterized by high repetition and dropout rates, as well as low learning levels. Despite efforts by the Ministry of Education to promote inclusion, these learners often have limited access to quality pedagogical support. This is further confounded by the fact that there is a paucity of research examining how teachers perceive and interact with these learners. This ethnographic study investigated teachers’ perceptions of inclusion in two public schools and how these perceptions shaped their pedagogical practices. The authors draw on observations and interviews to illuminate how teachers’ perceptions of their students, their schools, and their classroom environments influence their commitment to facilitating student learning, irrespective of student age or ability. The findings contribute valuable insights to inform strategies for enhancing inclusive education in the Dominican Republic.